Perlindungan Hukum Pelaku Pembangunan Atas Perubahan Lahan Untuk Perumahan Menjadi Lahan Sawah Dilindungi - Dodi Purnomo; Sadino Sadino (Fakultas Hukum Universitas Islam Jember, 2026)
The state's strategy in designating protected rice fields is to ensure national food security. However, the implementation of this designation overlaps with housing development permits held by housing developers. The purpose of this study is to provide legal certainty for housing developers regarding the conversion of land originally owned by developers for housing to protected rice fields. The methods in this study are a legislative approach, a case approach, and a conceptual approach. The conclusion is that housing developers can protect their land from the designation of protected rice fields by submitting an application to the Ministry of Agrarian Affairs and Spatial Planning to request a change in land use.